The new science of the mind from extended mind to embodied phenomenology - Rowlands, Mark (MIT Press, 2010)
"There is a new way of thinking about the mind that does not locate mental processes exlusively "in the head." Some think that this expanded conception of the mind will be the basis of a new science of the mind. In this book, leading philosopher Mark Rowlands investigates the conceptual foundations of this new science of the mind." "Traditional attempts to study the mind are based on the idea that mental processes---perceiving, remembering, thinking, reasoning---exist in brains; they are often described as "software" realized by the "hardware" of the brain. The new way of thinking about the mind has emerged from the confluence of various disciplines in cognitive science ranging from perceptual and developmental psychology to robotics. It emphasizes the ways in which mental processes are embodied (made up partly of extraneural bodily structures and processes), embedded (designed to function in tandem with the environment), enacted (constituted in part by action), and extended (located in the environment)." "The new way of thinking about the mind, Rowlands writes, is actually an old way of thinking that has taken on new form. Rowlands describes a conception of mind that had its clearest expression in phenomenology---in the work of Husserl, Heidegger, Sartre, and Merleau-Ponty. He builds on these views, clarifies and renders consistent the ideas of embodied, embedded, enacted, and extended mind, and develops a unified philosophical treatment of the novel conception of the mind that underlies the new science of the mind"--BOOK JACKET.